Quality management initiatives in Malaysia’s manufacturing firms - Julian Paul Sidin; Syed Azizi Wafa Syed Khalid Wafa; Stephen Laison Sondoh Jr. (Penerbit UMS, 2015)
This paper explores the implications of quality management on employee involvement, new product development and quality of production in Malaysia’s manufacturing firms. Based on the results of research into the implementation of quality management initiatives by 201 manufacturing firms in Malaysia, this paper concentrates on the relationships between quality management and the aforesaid variables. The most significant implication of this paper is that businesses should pay more attention to quality management practices, particularly in Malaysia’s manufacturing firms.